TRADISI SEBAMBANGAN MASYARAKAT ADAT LAMPUNGPEPADUN DI KELURAHAN KELAPA TUJUH KECAMATAN KOTABUMI SELATAN KABUPATEN LAMPUNG UTARA - Rizki Dwi Saputri; Ridhah Taqwa; Eva Lidya (Jurnal Media Sosiologi (JMS), 2021)
This research is entitled “Sebambangan Tradition of the Indigenous People of Lampung Pepadun in Kelapa Tujuh Village South Kotabumi Districts, North Lampung Regency”. The source of the data used in this research is the primary data and secondary data. The primary data sources in this study were obtained through interviews and observations of weddings using the sebambangan tradition. Secondary data sources are derived from documents related to the research. This study uses the theory of Social Solidarity according to Emile Durkheim with descriptive qualitative research methods and uses a case study approach. The validity of the data was tested with triangulation. Determination of informants in the research carried out with the objective of purposive deeper information in accordance with the research problem. The results of this study indicate that sebambangan is a tradition carried out by the indigenous people of Lampung Pepadun because it is contrained to carry out mariages. The sebambangan tradition is just a tradition that is formed from the habits of the Lampung indigenous people which is carried out from generation to generation and is completed using a customary process because there is no binding or regulating law. Even so, this tradition is valuable for the life of the Lampung indigenous people, so it is still carried out and preserved.